How Do Climate Variables Affect the Transmission of Dengue Infection in South and Southeast Asia: A Scoping Review - Fernando, Mekala; R.M, Nayani Umesha Rajapaksha (Asian Journal of Interdisciplinary Research, 2023)
Introduction: Dengue is an arboviral infection, transmitted from person to person via mosquito vectors. Dengue transmission is affected by rainfall, temperature, humidity and wind speed. These climate variables are changing as a result of anthropogenic climate change, and it is expected that this will affect the incidence of dengue. This scoping review explored the impacts on dengue transmission of variation in these climate variables in 12 Asian countries located in South- and South-East Asia regions. Methods: The protocol developed by the Joanna Briggs Institute was followed for this scoping review. Articles were found using the PubMed, Scopus, and Embase databases, as well as grey literature. Studies conducted in India, Bangladesh, Bhutan, the Democratic Republic of Korea, Indonesia, Maldives, Myanmar, Nepal, Thailand, Sri Lanka, and Timor Leste and published in English between 2002 and 2022 were included. An extensive literature search was conducted in February and March, 2022. A modified checklist designed for assessing the quality of ecological studies was used to assess the quality. Following quality assessment, ninety articles were included in the review. Results: The initial search yielded 1912 articles. After the duplicates were removed, 983 were identified as potentially relevant. Following the exclusion of 729 articles by two reviewers, 254 articles were subjected to full text screening. Thereafter, 90 articles were selected for the review that strictly met the inclusion criteria. Although the results were mixed, we found that dengue transmission decreases in temperature extremes. Dengue transmission increases with heavy rainfall, with a 1- 3-month lag. Humidity was also found to be related to dengue transmission. Other factors found to be associated with dengue transmission include the hours of sunshine and wind speed. Conclusion: There is a complex relationship between changing climate parameters and dengue incidence in Asia. This reflects the complex ecology of vector-borne diseases and suggests that the impact of changes in climate variables on dengue transmission may vary according to local climate and other factors.